Profiling bacterial diversity in a limestone cave of the western Loess Plateau of China - Wu, Yucheng; Tan, Liangcheng; Liu, Wuxing; Wang, Baozhan; Wang, Jianjun; Cai, Yanjun; Lin, Xiangui (Frontiers in Microbiology, 2015)
Bacteria and archaea sustain subsurface cave ecosystems by dominating primary production and fueling biogeochemical cyclings, despite the permanent darkness and shortage of nutrients. However, the heterogeneity and underlying mechanism of microbial diversity in caves, in particular those well connect to surface environment are largely unexplored. In this study, we examined the bacterial abundance and composition in Jinjia Cave, a small and shallow limestone cave located on the western Loess Plateau of China, by enumerating and pyrosequencing small subunit (SSU) rRNA genes. The results clearly reveal the contrasting bacterial community compositions in relation to cave habitat types, i.e., rock wall deposit, aquatic sediment and sinkhole soil, which are differentially connected to the surface environment. The deposits on the cave walls were dominated by putative cave-specific bacterial lineages within the -Proteobacteria or Actinobacteria that are routinely found on cave rocks around the world. In addition, sequence identity with known functional groups suggests enrichments of chemolithotrophic bacteria potentially involved in autotrophic C fixation and inorganic N transformation on rock surfaces. By contrast, bacterial communities in aquatic sediments were more closely related to those in the overlying soils. This is consistent with the similarity in elemental composition between the cave sediment and the overlying soil, implicating the influence of mineral chemistry on cave microhabitat and bacterial composition. These findings provide compelling molecular evidence of the bacterial community heterogeneity in an East Asian cave, which might be controlled by both subsurface and surface environments.